2017
DOI: 10.3389/fphys.2017.00284
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fully-Coupled 3D In-Stent Restenosis Simulations to In-vivo Data

Abstract: We describe our fully-coupled 3D multiscale model of in-stent restenosis, with blood flow simulations coupled to smooth muscle cell proliferation, and report results of numerical simulations performed with this model. This novel model is based on several previously reported 2D models. We study the effects of various parameters on the process of restenosis and compare with in vivo porcine data where we observe good qualitative agreement. We study the effects of stent deployment depth (and related injury score),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 47 publications
3
72
0
Order By: Relevance
“…This is similar to results obtained in an earlier studies for a similar 3D model. 34 There it was also demonstrated that a difference in re-endothelialization speed changes growth to a large extent, while the effects of the deployment depth are smaller, but still quite pronounced. As the re-endothelialization has such significant impact on the neointimal area, this part of the ISR model requires further study and validation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is similar to results obtained in an earlier studies for a similar 3D model. 34 There it was also demonstrated that a difference in re-endothelialization speed changes growth to a large extent, while the effects of the deployment depth are smaller, but still quite pronounced. As the re-endothelialization has such significant impact on the neointimal area, this part of the ISR model requires further study and validation.…”
Section: Discussionmentioning
confidence: 96%
“…9, and also by using computational models. 3,5,13,18,34 The computational models of ISR usually represent cells by agents, either freely moving 5,18,34 or placed on a lattice. 3,13 These agents take cues from the blood flow, concentration of drugs eluted from the stent, and from the vessel damage and mechanics, which affect the growth and proliferation of the cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the surrogate used, the simulation time of the semi-intrusive method was up to five times faster than of a Monte Carlo method. In future work, the semiintrusive metamodeling method will be applied to the three dimensional version of the ISR model employing the VECMAtk, since a black-box approach is not feasible for this application due to high computational demand [34].…”
Section: Variety Of Other Applicationsmentioning
confidence: 99%
“…Mathematical models for hemodynamics trace back to the work of Euler, who described a onedimensional treatment of blood flow through an arterial network with rigid tubes [11,33]; more sophisticated one-dimensional models are still used to study a variety of physio-pathological phenomena [1,2,13,21,23,29,30,37]. Computational advances have also allowed for the development of computationally intensive three-dimensional models [12,14,32,34,39,40], which have been used to accurately simulate specific human arteries (e.g., the carotid arteries [18]) and model their material properties (e.g., of cerebral arterial walls [38]). There also exist multicomponent models [10], which are amenable to applications such as modeling oxygen transport to solid tumors [6] and surgical tissue flaps [24,25].…”
Section: Introductionmentioning
confidence: 99%